Comments on two recent publications on GM maize and Roundup - Eriksson, Dennis (Sci Rep, 2018)
Two -omics studies on genetically modified maize and Roundup-fed rats, recently published in the journal Scientific Reports, contain serious flaws in the experimental design, methodology and interpretation of results, which we point out here. The use of -omics technologies are of increasing importance in research, however we argue for a cautious approach to the potential application in food safety assessments as these exceptionally sensitive and complex methods require a thorough and detailed evaluation of the biological significance of obtained results. Arising from: Mesnage et al. Sci Rep 7:39328 (2017), Mesnage et al. Sci Rep 6:37855 (2016).